2016
DOI: 10.1016/j.critrevonc.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Natural products and complementary therapies for chemotherapy-induced peripheral neuropathy: A systematic review

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a serious dose-limiting side-effect without any FDA-approved treatment option. Prior reviews focus mostly on pharmacological interventions, but nonpharmaceutical interventions have also been evaluated. A Web of Science and PubMed database search to identify relevant RCTs from January 2005 to May 2015 included the terms: CIPN, cancer; and supplements, vitamin E, goshajinkigan, kampo, acetyl-L-carnitine, carnitine, alpha-lipoic acid, omega-3, glutamine, or glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 79 publications
2
95
0
4
Order By: Relevance
“…About the safety of GJG, a recent phase 2, randomized, double-blind, placebo-controlled study concluded that GJG offers an acceptable safety margin and a promising effect in delaying the onset of grade 2 or greater oxaliplatin-induced peripheral neurotoxicity without impairing chemotherapy efficacy [48], confirming previous animal models findings [56]. To date, there are no strong recommendations about the use of specific neuroprotective agents and also the effectiveness of herbal medicines, such as GJG must be better elucidated [57][58][59]. Nevertheless, standard approaches, including amifostine and antidepressants have had limited efficacy and may themselves induce adverse side-effects, while herbal medicines has shown a better efficacy and safety profile.…”
supporting
confidence: 51%
“…About the safety of GJG, a recent phase 2, randomized, double-blind, placebo-controlled study concluded that GJG offers an acceptable safety margin and a promising effect in delaying the onset of grade 2 or greater oxaliplatin-induced peripheral neurotoxicity without impairing chemotherapy efficacy [48], confirming previous animal models findings [56]. To date, there are no strong recommendations about the use of specific neuroprotective agents and also the effectiveness of herbal medicines, such as GJG must be better elucidated [57][58][59]. Nevertheless, standard approaches, including amifostine and antidepressants have had limited efficacy and may themselves induce adverse side-effects, while herbal medicines has shown a better efficacy and safety profile.…”
supporting
confidence: 51%
“…As of June 14, 2016, we found 269 randomized controlled trials; however, none of these trials showed the efficacy of complementary modalities in treating CIPN, although a few showed incidental improvements. 30 Although there are many neuroleptic agents that have demonstrated efficacy in neuropathic pain due to other etiologies such as diabetes (gabapentin and pregabalin), duloxetine is the only pharmaceutical that has shown a significant benefit for CIPN and is the only agent recommended by American Society of Clinical Oncology guidelines 31 ; otherwise, there is no consistent evidence supporting any pharmaceutical's efficacy in treating CIPN symptoms. In the registration trial of duloxetine for CIPN, which also examined effects in any cancer type and after paclitaxel, taxane, or oxaliplatin treatment, the mean reduction in the average-pain ratings was 1.06 for duloxetine and 0.34 for a placebo with a moderate effect size of 0.51.…”
Section: Discussionmentioning
confidence: 99%
“…Electro-acupuncture (EA) involves using acupuncture needles attached to an electro-stimulator device that generates a low electrical current between the needles. Recently, studies have shown that acupuncture with and without electrical stimulation may effectively relieve CIPN symptoms [22,12]. Administering EA during chemotherapy to prevent CIPN symptoms has not been tested.…”
Section: Introductionmentioning
confidence: 99%